Epistemologia da Educação Física brasileira: uma (re)leitura a partir de pesquisadores do campo e de Paul Feyerabend - Garcia, Silas Alberto (2023)
The main objective of this dissertation was to investigate the epistemological debate in Brazilian Physical Education and evaluate whether there are contributions from Feyerabend's epistemology to the field. With this intention, the research itinerary was organized into four sections. In the first section, the research was predominantly qualitative and conducted through two fronts: bibliographic research and nonexperimental research (field study), with semi-structured interviews being the chosen technique for data collection. Interviews were conducted with eight researchers who have published impact studies on the epistemology of Brazilian Physical Education, including Valter Bracht, Mauro Betti, Paulo Fensterseifer, Pedro Hallal, Felipe Quintão de Almeida, Juliano de Souza, Marcelo Moraes e Silva and Ricardo Rezer. Data analysis followed the five-phase cycles proposed by Yin (2016). In the second section, the aim was to identify, through scientific production and interviews with researchers in the field, the main problems in the epistemological scenario of Brazilian Physical Education. In the third section, biographical episodes related to Paul Feyerabend's personal, professional, and academic-scientific formation were presented. In the fourth section, new perspectives and reflections for the current dilemmas of the epistemological debate in Brazilian Physical Education were discussed based on the researchers' views and Feyerabend's works. In conclusion, it was found that Feyerabend's thought, despite being controversial and sometimes misinterpreted, offers significant contributions to understanding and valuing the plural condition of Brazilian Physical Education, countering instrumental rationality and its logic of reification, as well as to thinking about a more qualified scientific formation for the field.